The influence of whole-body cryotherapy or winter swimming on the lipid profile and selected adipokines - Ptaszek, B.; Podsiadlo, S.; Wójcik, A.; Czerwinska-Ledwig, O.; Teleglów, A. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Purpose The aim of this study was to investigate the effect of a series of 20 whole-body cryotherapy (WBC) sessions and 20 winter swimming sessions on the lipid profile and selected adipokines.